Pemodelan Bencana Longsor Berbasis Spasial - Lusy, Irma; Suwarni, Nani; Miswar, Dedy; Jaya, M. Thoha B.S (UNIVERSITAS NEGERI MAKASSAR, 2020)
Tanggamus Regency as one of the regencies in Lampung Province is also one of the areas to landslides. Most areas of Tanggamus Regency have the potential for disasters, especially in coastal areas, rivers and hilly areas. This study aims to create a spatial landslide disaster model in Ulu Belu District, Tanggamus Regency, Lampung Province. The method used is overlay and scoring with a spatial approach. The results showed that the level of landslide hazard in Ulu Belu District was divided into three, namely landslide areas with 11,736 ha or 11%. While areas that are to landslides are 81.319 ha or 77%. Then the high landslide area is 11,907 ha or 12%, and the village that has the highest area for high landslide criteria is in Gunung Tiga Village with an area of 1,930 ha. While the village with the highest area for medium landslide levels is Petay Kayu Village with an area of medium landslide areas is 4,803 ha. As for the area which has the highest area for medium landslide criteria is Sinar Galih Village with an area of 292 ha